Mechanical downsizing of a gadolinium(iii)-based metal-organic framework for anticancer drug delivery - Kundu, Tanay; Mitra, Shouvik; Patra, Prasun; Goswami, Arunava; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2014)
A Gd-III-based porous metal-organic framework (MOF), Gd-pDBI, has been synthesized using fluorescent linker pDBI (pDBI=(1,4-bis(5-carboxy-1H-benzimidazole-2-yl)benzene)), resulting in a three-dimensional interpenetrated structure with a one-dimensional open channel (1.9x1.2nm) filled with hydrogen-bonded water assemblies. Gd-pDBI exhibits high thermal stability, porosity, excellent water stability, along with organic-solvent and mild acid and base stability with retention of crystallinity. Gd-pDBI was transformed to the nanoscale regime (ca. 140nm) by mechanical grinding to yield MG-Gd-pDBI with excellent water dispersibility (>90min), maintaining its porosity and crystallinity. In vitro and in vivo studies on MG-Gd-pDBI revealed its low blood toxicity and highest drug loading (12wt%) of anticancer drug doxorubicin in MOFs reported to date with pH-responsive cancer-cell-specific drug release.
Keywords: ball-milling; doxorubicin; drug delivery; metal-organic frameworks; nanocarriers

Multifunctional and robust covalent organic framework-nanoparticle hybrids - Pachfule, Pradip; Panda, Manas K.; Kandambeth, Sharath; Shivaprasad, S. M.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry A, 2014)
Highly dispersed Pd(0) nanoparticles were successfully immobilized into a stable, crystalline and porous covalent organic framework (COF), TpPa-1, by a solution infiltration method using NABH(4) as a reducing agent. High resolution and dark field TEM images confirmed the uniform loading of the Pd(0) nanoparticles into the TpPa-1 matrix without aggregation. This hybrid material exhibited excellent catalytic activity towards the Cu free Sonogashira, Heck and sequential one pot Heck-Sonogashira cross-coupling reactions under basic conditions, and with superior performance compared to commercially available Pd supported on activated charcoal (i.e., 1, 5 and 10 wt%). Additionally, the precursor Pd(II)-doped COF also displayed competitive catalytic activity for the intramolecular oxidative biaryl synthesis under acidic conditions. Both catalysts were found to be highly stable under the reaction conditions showing negligible metal leaching, non-sintering behavior, and good recyclability. To the best of our knowledge, the organic support used in this work, TpPa-1, constitutes the first COF matrix that can hold both Pd(0) nanoparticles and Pd(II) complex without aggregation for catalytic purposes under both highly acidic and basic conditions.